The role of Ukrainian Scientific Society in formation of institutions of natural agricultural sphere in the structure of Ukrainian Academy of Sciences - Novorodovskyi, V. V. (History of science and technology, 2016)
The basic premises of the institutional design of natural-agricultural institutions of the Ukrainian Academy of Sciences (UAS) are revealed. Particular attention is paid to the role of Ukrainian Scientific Society (USS) in the formation of institutions of UAS. The investigation of organizational formation of natural sciences in the structure of Society during 1907-1918 is made. Also, the features of activities and evolution of natural section of USS after formation of UAS are revealed. On the basis of a comprehensive analysis of sources was found out the key value of separate scientists of natural section of USS in creating a network of natural-agricultural establishments of Academy of Sciences. The result of the research has been the disclosure of features of scientific activities of scientists-naturalists of Society and their influence on the formation of the concept of the Academy of Sciences. In the article was found out the particular importance of scientific achievements of natural section members, later the Department of Natural Sciences of USS, in forming the grounds for future researches of academic institutions of natural-agricultural purpose.